Influence of Climatic Factors on Malaria Epidemic in Gulu District, Northern Uganda: A 10-Year Retrospective Study - Simple, Ouma; Mindra, Arnold; Obai, Gerald; Ovuga, Emilio; Igwaro Odongo-Aginya, Emmanuel (Malaria research and treatment, 2018)
Globally, 15 countries, mainly in Sub-Saharan Africa, account for 80% of malaria cases and 78% of malaria related deaths. In Uganda, malaria is endemic and the mortality and morbidity due to malaria cause significant negative impact on the economy. In Gulu district, malaria is the leading killer disease among children <5 years. In 2015, the high intensity of malaria infection inNorthernUganda revealed a possible link between malaria and rainfall.However, available information on the influence of climatic factors onmalaria are scarce, conflicting, and highly contextualized and therefore one cannot reference such information to malaria control policy in Northern Uganda, thus the need for this study. Methods and Results. During the 10 year’s retrospective study period a total of 2,304,537 people suffered frommalaria in Gulu district.Malaria infection was generally stable with biannual peaks during the months of June-July and September-October but showed a declining trend after introduction of indoor residual spraying. Analysis of the departure of mean monthly malaria cases from the long-term mean monthly malaria cases revealed biannual seasonal outbreaks before and during the first year of introduction of indoor residual spraying. However, there were two major malaria epidemics in 2015 following discontinuation of indoor residual spraying in the late 2014. Children <5 years of age were disproportionally affected bymalaria and accounted for 47.6% of the totalmalaria cases. Both rainfall (P=0.04) and relative humidity (P=0.003) had significant positive correlations with malaria.Meanwhile, maximumtemperature had significant negative correlation with malaria (P=0.02) but minimum temperature had no correlation with malaria (P=0.29). Conclusion. Malaria in Gulu disproportionately affects children under 5 years and shows seasonality with a generally stable trend influenced by rainfall and relative humidity. However, indoor residual spraying is a very promising method to achieve a sustained malaria control in this population.
Keywords: Climatic Factors; Malaria Epidemic; Gulu District